EIB Group Activity Report 2019 - European Investment Bank (European Investment Bank, 2020)
This report tracks the green thread that runs through the European Investment Bank Group's work in 2019, specifically action to fight climate change. Climate action has long been a significant factor in the Bank's work. In 2019, we responded to an unprecedented emergency with new ambitions for climate investment over the coming decade and a new energy lending policy. This report tells stories of ingenuity and commitment, job creation and prosperity. Woven together with the green thread of sustainable EIB climate investment, it illustrates the opportunity climate action presents for all of us to safeguard our world for future generations and to build a prosperous, clean economy.